2014
DOI: 10.1021/jp4115282
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Metal Free Naphthalocyanine Vapor Deposited on Au(111)

Abstract: Naphthalocyanines (Ncs) are promising candidates for future components in electronic devices and applications. To maximize the efficiency of Nc devices, it is critical to understand their structural and electronic properties and how these are impacted by deposition methods. The formation of a metal free naphthalocyanine (H 2 Nc) self-assembled monolayer on a Au(111) crystal was investigated by scanning tunneling microscopy under ultra-high-vacuum conditions at room temperature. A rigorous purification and proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The rhombic unit cell (17 Â 55 Å 2 , 951) observed for the stable island structure contained three molecules [292]. A well-ordered 2HNc structure with even higher packing density was observed on Au (1 1 1) [293]. The rhombic (near-square) unit cell (32.5 Â 31.7 Å 2 , 92.51) contained four molecules.…”
Section: Adsorption Of Simple Metallophthalocyanines On Metalsmentioning
confidence: 93%
See 2 more Smart Citations
“…The rhombic unit cell (17 Â 55 Å 2 , 951) observed for the stable island structure contained three molecules [292]. A well-ordered 2HNc structure with even higher packing density was observed on Au (1 1 1) [293]. The rhombic (near-square) unit cell (32.5 Â 31.7 Å 2 , 92.51) contained four molecules.…”
Section: Adsorption Of Simple Metallophthalocyanines On Metalsmentioning
confidence: 93%
“…Adsorption of 2HNc (see Fig. 9) was studied on Au(1 0 0) [292] and Au(1 1 1) [293,294]. On the hexagonally reconstructed Au(1 0 0) surface, a submonolayer coverage (0.5 ML) of 2HNc deposited at room temperature formed clusters, stripes, and densely packed islands, which were aligned along the two high-symmetry directions of the substrate.…”
Section: Adsorption Of Simple Metallophthalocyanines On Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have so far been very few studies of the properties of sublimed Nc thin films 11,14,15 ; in fact it has been suggested that Nc cannot be sublimed 13 , although the deposition of monolayer coverages have been reported by a number of groups [16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The technique can be used in various environments such as vacuum, 6 air, 7 solution, 8 and even under gel. 9 Among these environments, ultrahigh vacuum (UHV)-solid and solution-solid (SS) interfaces get the most attention.…”
Section: Introductionmentioning
confidence: 99%